442 Primary vaginal cancer: a single institution case series of patient, tumour and treatment factors affecting outcomes. (18th September 2019) - Obermair, H; Harrison, M; Lim, K; Herbst, U
Abstract : Objectives: Primary vaginal carcinomas are rare, accounting for 1–2% of gynaecological malignancies. This project aimed to describe a series of primary vaginal cancer cases at a single institution, identifying patient, tumour and treatment factors impacting outcomes. Methods: A retrospective chart analysis was performed for all patients diagnosed with primary vaginal cancer from 2008 to 2018 at a single institution in Australia. For each case, data extracted included histopathology, staging, treatment received, socio-demographic information and patient outcomes. Overall, eight patients were eligible to be included in analysis. Results: Average age at diagnosis was 59 years (34–75 years). 87.5% were in the most socially disadvantaged quintile of the Index of Socio-Economic Disadvantage. Overall, 75% of patients had squamous cell carcinoma and 25% had melanoma. Stage at presentation: FIGO stage one (n=3), stage two (n=2) and stage three (n=3). The average Body Mass Index was 26.2 kg/m2 and Charlson Comorbidity Score of 4.75. Treatment received included: surgery alone (n=2), primary chemo-radiotherapy (n=3), surgery and adjuvant radiation (n=1), surgery and adjuvant immunotherapy (n=1), and chemotherapy alone (n=1). With median 39 months follow-up (11–113 months), 2 of 6 patients with SCC have relapsed and 2 of 2 patients with melanoma have relapsed. Conclusions: This study indicates that outcomes for vaginal cancers are poor, and that early presentation is essential to improve outcomes. Treatment is highly individualised based on extent of disease at presentation. Due to limited literature in this area, it is difficult to compare patient demographics, tumour factors and standard treatment.